Efektivitas Pemberian Jus Mentimun Terhadap Tekanan Darah pada Pasien Hipertensi di Lingkungan Klinik Duha Medika Center Lampung - Feri Nurjaya; Eko Wardoyo; Sugiarto Sugiarto (Jurnal Medika Nusantara, 2025)
Hypertension is a serious medical condition and can increase the risk of heart, brain, kidney and other diseases. Hypertension can be treated by administering medical (pharmacological) and non-pharmacological drugs. One of the non-pharmacological treatments is using cucumber juice. Cucumbers are diuretic because of their high water content, which helps lower blood pressure. The aim of this research is to determine the effectiveness of giving cucumber juice on blood pressure in hypertensive patients at the Duha Medika Center Lampung Clinic in 2024. This research design uses a quasi-experimental design with a one group pre test - post test design without control group. The population in this study were patients at the Griya Sehat Kemiling Clinic. The population was 124 and the sample was 55 respondents using purposive sampling technique. This research was carried out in November 2024 at the Duha Medica Center Clinic. Data were collected using observation sheets and blood pressure measuring instruments, namely sphygmomanometers, univariate and bivariate data analysis (Wilcoxon Test). The results of statistical tests using the Wilcoxon test obtained a p-value = 0.000, so it can be concluded that there is an effect of giving cucumber juice on blood pressure in hypertensive patients at the Duha Medika Center Clinic in 2024. Hypertensive patients are expected to be able to utilize natural ingredients to manage hypertension such as cucumber juice.